Pragmatic Politeness in the Local Election: An Analysis of the Defeat of Agus-Silvy in 2017 DKI Jakarta Gubernatorial Elections - Aini, Aldila Arin; Sumarlam, Sumarlam; Purnanto, Dwi (Jurnal Politik Indonesia: Indonesian Political Science Review, 2019)
This research aims to analyze factors caused Agus-Sylvi’s losing in 2017 DKI Jakarta gubernatorial election. This research analyzes Agus-Sylvi’s losing not only from politic sides, but also from pragmatics’ politeness. Pragmatic politeness in this research is according to Brown and Levinson’s theory (1987) which is based on the speakers and hearers’ faces. In collecting the data, the reseacher chooses considerably free method and note taking technique. Pragmatic based approach and contextual method are used to analyze the data. From all the data, the researcher had found 83 forms of politeness strategies which showed the form of politeness strategy used by Agus-Sylvi. Those politeness strategies are positive, negative, bald-off record, and across politeness strategies. The use of the most positive politeness strategy, offer and promise, revealed the way of Agus-Sylvi got lost in 2017 governor election of DKI Jakarta. It means that it is not good to use positive politeness too much because the hearers will judge the speakers as a person who loves to boast. The lack of negative politeness and bald-off politeness also revealed that Agus-Sylvi did not respect other participants of Jakarta’s2017 governor election. The non-dominant across politeness strategy proved that Agus-Sylvi could not compete in confessing their meaning pragmatically.